Artificial Intelligence Uprising:How to build a Sci-fi robot - Singla, Nikhil; Jain, Nipun; Thakral, Paras (IJRDO -Journal of Computer Science Engineering, 2015)
This paper reviews about the step by step instructions to build a robot that could be similar to the robots shown in the sciencefiction movies. They are able to think themselves and act upon the situations, their brain is superfast and nothing on theentire universe can be more powerful than them. Artificial intelligence is the most growing technology in the modern scienceand technology. This technology has given us many ways to approach to the time where we can think of building such a robot.The advanced science that are still in the developing era such as neural networks and quantum computing can allow us tobuild robots that are more intelligent than the today’s computers combined. Along with the most intelligent brain our robotwill also need a versatile body, a body that can function in any situation and any environment. The latest technology thatenables us to do is known as claytronics